Spectrophotometric determination of zinc and copper in a multisyringe injection analysis system using a liquid waveguide capillary cell: Application to natural waters - Páscoa, Ricardo N. M. J. (2012)
This work exploits a multisyringe injection analysis (MSFIA) system coupled with a long liquid waveguide capillary cell for the spectrophotometric determination of zinc and copper in waters. A liquid waveguide capillary cell (1.0mpathlength, 550mmi.d. and 250mL internal volume) was used to enhance the sensitivity of the detection. The determination for both ions is based on a colorimetric reaction with zincon at different pH values. The developed methodology compares favourably with other previously described procedures, as it allows to reach low detection limits for both cations (LODs of 0.1 and 2mg L−1, for copper and zinc, respectively), without the need for any preconcentration step. The system also provided a linear response up to 100mg L−1 with a high throughput (43 h−1) and low reagent consumption and effluent production. The developed work was applied to natural waters and three certified reference water samples.